2017
DOI: 10.18203/2394-6040.ijcmph20174629
|View full text |Cite
|
Sign up to set email alerts
|

A study on the prevalence of chronic obstructive pulmonary disease among adults in Madurai, Tamil Nadu

Abstract: Background: Chronic obstructive pulmonary disease (COPD) is a major public health problem with increasing prevalence especially in developing countries. Burden of disease estimation is important for decision making, planning, prioritising and allocating funds. It has been found that the recent data on prevalence of COPD is less in south India, especially Tamil Nadu. Hence this study was undertaken in order to estimate the prevalence of COPD in Madurai among adults and its association with socio demographic var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…In the current study, the overall prevalence of the COPD among men above 30 years of age was 15.8% which is comparable to the study done by Satoru Fukuyama et al of 14.6% [8] . In contrast a study conducted by Mohamed Saleem et al reported a higher prevalence of 39.2% [13] .…”
Section: Discussionmentioning
confidence: 65%
“…In the current study, the overall prevalence of the COPD among men above 30 years of age was 15.8% which is comparable to the study done by Satoru Fukuyama et al of 14.6% [8] . In contrast a study conducted by Mohamed Saleem et al reported a higher prevalence of 39.2% [13] .…”
Section: Discussionmentioning
confidence: 65%
“…In the present study the Sample Size is Determined with the help of following method. According to Saleem et al, the prevalence of COPD is 22.1% [13]. Hence, we chose p=22.1 %, q= 1-p i.e.…”
Section: Sample Size Calculationmentioning
confidence: 99%
“…The prevalence in males was 39.2% and females was 12.2%. Prevalence was higher among increasing age, males, illiterate, smokers, poor ventilation and those using biomass fuels [13]. Though COPD is common among older age group, the prevalence in younger age is also of public health importance as they would be continuously exposed to the risk factors.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Such studies pertain mainly to the field of medical sciences but do help us in assessing the quantified effect of pollution on women. In a study of COPD, [3] observed its prevalence among adults in Tamil Nadu to be 22.1% with women facing 12.2% of the illness. In the context of other nations, [4] observed in a study of French households that IAP cost approximately EUR 20 billion in 2004.…”
Section: Introductionmentioning
confidence: 99%